Multidiscipline Care for Type 2 Diabetes Patients: from General to Asian Population - Benedicta Mutiara Suwita; Dewi Friska; Deriyan Sukma Widjaja; Liana Srisawitri (Acta Medica Indonesiana)
Multidiscipline care is defined as a care consisting of at least a physician, a nurse, and other healthcare worker (eg. dietician). Multidiscipline care has generated benefits, both in medical aspects (eg. increasing patients’ compliance) and nonmedical aspects (eg. more cost-effective than conventional treatment). There are several models of multidiscpline care; however, which model is more suitable for type 2 diabetes care is not clear yet. In this review, we aimed to identify and compare multidiscipline care method for reducing glycated hemoglobin ( HbA1C) levels in type 2 diabetes patients, particularly Asian patients because they have greater tendency to develop type 2 diabetes at lower degrees of obesity and at younger ages than Caucasian ethnic group. There were limited number of studies examining multidiscipline care for type 2 diabetes patients, moreover for Asian patients. They showed mixed results on the efficacy of multidiscipline care in achieving HbA1C target. Healthcare personnel visit, either personal or group session, appeared effective both for general and Asian T2DM patients. It needs further studies to clarify which models are most effective for practices of varying cultures, socio-economic condition, and healthcare settings.